KAJIAN AKSESIBILITAS DAN ERGONOMI PADA MEBEL PAUD AL ABIDIN SURAKARTA - R. Ernasthan Budi Prasetyo; I Nyoman Suyasa; Eko Sri Haryanto (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
Furniture is an important tool used as a supporter for the smooth activities of teaching and learning in schools. Furniture that does not meet the rules of accessibility and ergonomics can cause the activities of its users to be disturbed. Research Beginner Lecturers aims to determine the accessibility and ergonomics of furniture in early childhood / kindergarten Al Abidin in Surakarta. Research is used to find out whether students have difficulty or ease when using the furniture. Ergonomic measurement is important to see if the object is suitable dimensinya with the needs required by the user, especially for students PAUD Al Abidin Surakarta. The object of research is the furniture contained in PAUD Al Abidin Surakarta. The method used in descriptive with qualitative approach supported by quantitative data (numeric), or can also be called double research strategy that is use of various method in solving a research problem. Quantitafif here uses numerical data which is the result of field measurement, then compared with referenced references, resource persons and analyzed based on researcher interpretation. The results of this novice lecturer’s research is accessibility data and implementation of ergonomics science that can be used as input to the manager PAUD Al Abidin IN Surakarta. The results of this novice lecturer’s study is also expected to provide the content of Egonomi, Interior Design and Furniture on Interior Design Study Program ISI Surakarta.